1984
DOI: 10.1128/aac.26.6.845
|View full text |Cite
|
Sign up to set email alerts
|

Cefmenoxime pharmacokinetics in healthy volunteers and subjects with renal insufficiency and on hemodialysis

Abstract: The pharmacokinetics of cefmenoxime were characterized in five healthy volunteers and in 15 subjects with various degrees of renal insufficiency after a single 10-mg/kg, 5-min intravenous infusion. Five of these subjects were studied both on hemodialysis and during an interdialytic period. Plasma, urine and dialysate were assayed for cefmenoxime by a specific high-pressure liquid chromatographic assay. Peak plasma concentrations of cefmenoxime were ca. 94 ,ug/ml after completion of the infusion. The mean plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The serum cefmenoxime levels after intravenous administration were described in terms of a two-compartment open model, and the individual serum level profiles were fitted to a biexponential function of the form: C = A x e-a' + B x e-t, in which C is the concentration of antibiotic in serum at time t postdosing; a and 1 are the rate constants governing the distribution and elimination phases of drug loss from serum, respectively; and A and B are the intercepts of slopes a and P with the ordinate. Pharmacokinetic analysis was performed with a nonlinear least-squares program developed by Yamaoka et al (17) (7), although a somewhat longer tY2p, has been reported by others for healthy subjects (4,6,12,14). Thus, the t12, of cefmenoxime after intravenous dosing in subjects with normal renal function is comparable to that of cefotax- ime (0.9 to 1.2 h), but is shorter than those of other cephalosporins (1,8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The serum cefmenoxime levels after intravenous administration were described in terms of a two-compartment open model, and the individual serum level profiles were fitted to a biexponential function of the form: C = A x e-a' + B x e-t, in which C is the concentration of antibiotic in serum at time t postdosing; a and 1 are the rate constants governing the distribution and elimination phases of drug loss from serum, respectively; and A and B are the intercepts of slopes a and P with the ordinate. Pharmacokinetic analysis was performed with a nonlinear least-squares program developed by Yamaoka et al (17) (7), although a somewhat longer tY2p, has been reported by others for healthy subjects (4,6,12,14). Thus, the t12, of cefmenoxime after intravenous dosing in subjects with normal renal function is comparable to that of cefotax- ime (0.9 to 1.2 h), but is shorter than those of other cephalosporins (1,8).…”
mentioning
confidence: 99%
“…3). Thus, assuming that the standard individual dose schedule of cefmenoxime in subjects with normal renal function is 1.0 g intravenously every 6 h, the same standard individual dose may be given every 8 h for those with a CLCR of 60 ml/min per 1.73 m2, every 12 h for those with CLCR of 50 ml/min per 1.73 m2, and every 24 h for those with CLCR of 20 ml/min per 1.73 i2. Application of the same rule to those patients with severe renal failure would be rather inappropriate since it is expected to produce a drug level in-serum that is too low over a prolonged time.…”
mentioning
confidence: 99%
“…In 9 patients (1-9) the study was done after a single intravenous dose of 1 g CMX and in 3 patients (10-12) after repeated IV doses of 0.5 g b. d. Blood was obtained from the arterial line before and 2 min and 0.5, 1,2,4,8,12, and 24 h after bolus injection of CMX into the venous line of the haemofiltration system. Filtrate was collected over 12 or 24 h. Serum separated after centrifugation and filtrate were stored at -20 °C until analysed.…”
Section: Methodsmentioning
confidence: 99%
“…rain -1.1.73 m -2. The elimination half-life was 15.6 (7.5) h. During haemodialysis 16-51% of the administered dose was recovered in the dialysate (Gambertoglio et al 1984). No data are available about the elimination of CMX during continuous haemofiltration.…”
mentioning
confidence: 91%
“…Antibacterial drugs: 1 Pechere & Dugal (1979); 2 Noone (1984); 3 Rlstuccia & Cunha (1985); 4 Meyer (1981); 5 Hallynek et al (1981); 6 Craig at al. (1983); 7 Guay (1983); 8 Brogden et al (1976); 9 Tartaglione & Polk (1985); 10 Balant et al (1985); 11 Thompson & Wright (1983); 12 Clark et al (1983); 13 Derry (1981); 14 Leroy et al (1982); 15 Czerwinski & Federson (1979);16 Qulntillanl & Nightingale (1978); 17 Gambertoglio et al (1984); 18 Pontzer & Kaye (1984); 19 Lyon (1983); 20 Barriere & Mills (1982); 21 Doluiso (1982); 22 Konishi & Ozawa (1984); 23 Kampf et al (1981); 24 Ohkawa et al (1981); 25 Matzke & Keane (1983); 26 Richards …”
Section: Limitationsmentioning
confidence: 97%